The Role of Public Universities in Youth Civic Engagement and Social Responsibility: A Study of Social Sciences Faculty, University of Peshawar, Pakistan (Journal of Social Sciences Review, 2023)
The present study aims to explore the role of public sector universities in the social responsibilities and civic engagement of youth in the faculty of social sciences, University of Peshawar, Pakistan. Using a quantitative survey involving systematic sampling methods, the study interviewed 180 social sciences at KP public universities. For the collection of data from the respondents, a self-administered questionnaire was used. The findings indicated that most of the participants of the study had never participated in any volunteer community service, or even signed up for a social issue. In the view of the participants, the role of you in society should be to advocate for positive change and peace. Participants advocated for peace and interfaith education, fostering linkages and capacity-building opportunities with the business and development sectors, as well as folklore, music and theatre at the country's public universities. The study recommendation includes; stimulating social responsibility and the opportunities for civic engagement for students at the country's public universities so that youth may involve effectively to the benefit of the wider community.
Keywords: Civic Engagement; Social Responsibilities; Public Universities; Youth; Pakistan